Effective treatment of claw horn lesions in dairy cattle - Thomas, Heather Jane (2017)
Lameness was described by the Farm Animal Welfare Council (2009) as one of the foremost health and welfare challenges facing dairy cattle in the UK. Studies suggest UK lameness prevalence has increased over the past 30 years peaking at 36.8% in 2006-2007. The first study in this thesis aimed to investigate current lameness prevalence and related management practices in the UK. Short, structured interviews were conducted with farmers on 43 randomly selected farms in central England during spring 2014 before mobility scoring the lactating herd. Mean herd lameness prevalence was 30.1% (range 7.3%-60.6%). This represents a drop in prevalence since 2007, suggesting a corner may have been turned in control of lameness. A large proportion of farmers reported conducting their own routine trimming and treatment of lame cows. It is therefore important to ensure correct training reaches these farmers if lameness prevalence is to continue to fall. Lameness is often associated with claw horn lesions (sole ulceration and white line disease) however little information is available in the scientific literature on treatment protocols for these lesions. This second study in this thesis aims to begin to address this knowledge gap through a partially blinded, randomised, positively controlled clinical trial (RCT). Animals with an acute case of lameness (two non-lame scores followed by a lame score determined by fortnightly mobility scoring) resulting from claw horn lesions on a single, hind claw were enrolled and allocated at random one of four treatments: 1) Therapeutic trim (TRM) (positive control group), 2) therapeutic trim and foot-block (TB), 3) therapeutic trim and nonsteroidal anti-inflammatory drug (NSAID) (TN) and 4) therapeutic trim, foot-block and NSAID (TBN). One hundred and eighty-three cows were enrolled over a 13-month period. Based on a sound score (score 0) at 35 days post treatment, the number (and proportion) of successful treatments was 11 of 45 (24.4%) TRM, 14 of 39 (35.9%) TB, 12 of 42 (28.6%) TN and 23 of 41 (56.1%) TBN. A significant difference was seen between treatment groups (P=0.01). The results of this study suggest that recovery in animals treated for lameness due to claw horn lesions is maximised by treatment with a TBN. Smaller non-significant improvements were also seen in TB and TN compared with a TRM. The lesions treated in this RCT were largely mild due to the early recognition and treatment protocol used. Studies have demonstrated delays in identification of lame cows on farms and so the lesions seen in this study may not represent those treated by farmers, foot trimmers and vets in the field. The third study in this thesis aimed to investigate the impact of chronicity of lameness on treatment outcomes. The prospective, partially blinded, positively controlled RCT followed a similar protocol to the previous RCT but enrolled cows lame on the same hind leg for at least two of the last three mobility scores. Animals were randomly allocated one of three treatments: 1) therapeutic trim only, 2) therapeutic trim and shoe or 3) therapeutic trim, shoe and NSAID. Three outcomes at 42 (±4) days post treatment were analysed: (i) non-lame (score 0 or 1 at outcome), (ii) improved (lower mobility score at outcome than enrolment) and (iii) apparent leg cure (non-lame on treated leg or lame on contralateral leg at outcome). Over a 13-month period, data was collected for 189 cases of lameness from 176 cows (13 cows received treatment on both hind limbs). No significant difference between treatment groups was seen for any of the outcomes analysed. A very low response rate to treatment of around 15% was seen across all treatment groups. Data for all animals treated in this chronic lameness RCT (CLRCT) was compared to a subset of data from the acute lameness RCT (ALRCT). Analysis showed a significant difference for outcomes (i), (ii) and (iii) in animals treated for acute compared to chronic lesions (P<0.01). In the ALRCT, 31 of 127 treated animals were lame at outcome (15 lame on the opposite hind leg to enrolment). In the CLRCT 132 of 156 treated animals were lame at outcome (60 lame on the opposite hind leg to enrolment). These findings support the need for both early and effective treatment and suggest that animals should receive appropriate treatment interventions in both hind limbs even if presenting with unilateral lameness. To have an impact on lameness prevalence, it is essential that research findings are disseminated to farmers treating cows on farms. The final study in this thesis aimed to assess the efficacy of different methods of knowledge transfer (KT) in relation to this. A prospective, qualitative and quantitative study was conducted to assess three methods of cattle lameness KT; 1) paper based/online AHDB dairy resources (positive control group), 2) resources plus facilitated discussion group, 3) resources plus on-farm visit by ‘expert’ veterinary surgeon. Prior to the KT session participants completed a semi-structured interview and observed video clips of lame and non-lame cows to select how quickly they would treat each case. Following the KT session the video exercise was repeated and a feedback form completed. Video clip responses were analysed pre-and post-session. Feedback forms were used to assess engagement and likelihood of behavioural change. Fifty-one individuals participated in the study. ‘Expert’ visits had a significant positive effect on the farmers’ awareness of the ‘correct’ maximum treatment interval advised for lame cows compared to resources alone. ‘Expert’ KT sessions were also felt to be significantly more enjoyable and useful. A narrow range of feedback scores suggest this method was also most accessible to a range of learners. The findings of this study suggest the role of the veterinary advisor remains central to the KT process. The key messages derived from the research undertaken in this thesis are the need for early identification and prompt, effective treatment of claw horn lesions in dairy cows. As the body of research grows it is imperative that suitable knowledge transfer strategies are employed to best disseminate these findings to farm-level and maximise their impact on the health and welfare of affected animals.